Application of Roland Barthes’ theories in media researches - Kazakevičiūtė, Evelina (Information & Media, 2015)
There are plenty of connotational and mythical meanings in verbal as well as visual media messages. The theories offered by Roland Barthes are most suitable for the analysis of these messages. Although his theories lay the foundations for the methodology which is needed to conduct the media analysis, a convenient set of methodological tools is not available so far. In this article, we have joined two works by R. Barthes: the theory of the modern myth, developed in his book “Mythologies” (1957), and the insights in his essay “The Photographic Message” (1977). This has resulted in the methodology instrumental in analyzing media messages. The myth-semiological system scheme allows us to demonstrate the internal structure of a myth created by the media. Moreover, the rhetoric figures of a myth allow us to recognise the ideological nature of mythical messages. Finally, the connotation procedures of media illustrations allow us to identify connotational meanings in photographs.